The legal framework for regulating smart energy grids and smart distribution units (RMU) and their role in promoting the transition towards sustainable energy in accordance with Vision 2030 - Tammam Abdul-Latif Al-Jijkli (International Journal of Law Research and Studies, 2026)
This paper examines the legal framework governing smart grid agreements and Ring Main Units (RMUs) in the Kingdom of Saudi Arabia and analyzes their role in supporting the transition toward sustainable energy in alignment with Vision 2030. As the energy sector undergoes a profound transformation driven by digitalization, decentralization, and sustainability imperatives, smart grids have become essential for enhancing efficiency, reliability, and the integration of renewable energy sources.The study adopts a descriptive-analytical approach to assess the current regulatory structure of the Saudi electricity sector, with particular focus on the legal nature of smart grid agreements. It addresses key issues such as contractual obligations, data governance, cybersecurity, and multi-party liability. Additionally, the paper explores the technical and legal significance of RMUs as critical components in modern electricity distribution systems, emphasizing their role in improving fault isolation, operational continuity, and network resilience.The research further provides a critical evaluation of existing legislation, identifying regulatory gaps related to digital energy systems and the absence of specialized legal frameworks. A comparative analysis of international regulatory models is also included to derive best practices applicable to the Saudi context.The findings suggest that, despite significant progress in energy sector reform, there is a pressing need for a comprehensive and flexible legal framework that accommodates emerging technologies and supports sustainable energy objectives. The study concludes with recommendations aimed at enhancing regulatory effectiveness and aligning legal structures with the goals of Vision 2030.
Keywords: Smart Grids; Ring Main Units (RMU); Energy Law; Digital Energy Regulation; Cybersecurity; Data Governance; Renewable Energy; Saudi Vision 2030; Sustainable Energy; Electricity Regulation